REVOLUSI KEPEMIMPINAN DALAM PENDIDIKAN - Hartono Hartono (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2012)
Abstract : leadership that emphasizes human relations is the leadership that was initiated by Ki Hajar Dewantara, namely Ing Ngarsa Sung Tulada means when in front place, the leader should be a role model, Ing Madyo Mangun Karsa meanswhen in the middle (among) of society, a leader must be able to generate a willingness to work, and Tut Wuri Handayani means when in the back place, the leader must be able to be a supporter. Implementing the concept of Ki Hajar Dewantara’s leadership thoroughly is very important, especially in education. The three characters are the character of a true leader. Leaders who attendedas an example, inspiration, and supporter for group members is to improve organizational performance. Key Words: Leadership and Education. : leadership that emphasizes human relations is the leadership that was initiated by Ki Hajar Dewantara, namely Ing Ngarsa Sung Tulada means when in front place, the leader should be a role model, Ing Madyo Mangun Karsa meanswhen in the middle (among) of society, a leader must be able to generate a willingness to work, and Tut Wuri Handayani means when in the back place, the leader must be able to be a supporter. Implementing the concept of Ki Hajar Dewantara’s leadership thoroughly is very important, especially in education. The three characters are the character of a true leader. Leaders who attendedas an example, inspiration, and supporter for group members is to improve organizational performance. Key Words: Leadership and Education.